Pengembngan Pengembangan Aplikasi Pembelajaran Interaktif Sistem Pengisian Berbasis Android: Development of Android-Based Interactive Learning Application for Charging Systems - Yeremia; Muhammad Hudan Rahmat; Supriyadi; I Made Supatra (Universitas Pendidikan Ganesha, 2026)
This study aims to develop an interactive learning application based on Android on the topic of the charging system with the support of the Godot game engine for vocational high school students. The research method used is Research and Development with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), conducted at SMK Negeri 1 Palangka Raya. The research instruments consisted of expert validation questionnaires and practicality tests for students and teachers. The validation results showed that the application falls into the category of highly feasible to use, with an average score of 4.00 from material experts and 4.35 from media experts. The practicality test through student responses in the small-scale trial obtained an average score of 3.72, and in the large-scale trial 3.88, both categorized as very good. In addition, teacher responses to the application obtained an average score of 4.10, categorized as practical. Thus, the interactive Android-based charging system learning application developed using the Godot game engine is declared feasible and practical to be used as a teaching medium to improve students’ understanding of automotive electrical systems.